Metamorfoses de Phoenix: representação feminina em fantasma do paraíso - VASCONCELOS, Nayara Maria (2015)
This research analyses and discusses the female character in the movie Phantom of the Paradise (Brian De Palma, 1974) through the feminist and gender debates of the American society in the 1970’s. In this sense, it directs the look at the protagonist Phoenix (Jessica Harper) in order to reveal how changes in social and cultural fields of the time converged and contributed to the construction of the female character in this work. Through the movie analysis, the purpose is to understand the character’s metamorphosis, wavering from a well-behaved girl to a femme fatale. This research is justified by the need to understand how the american filmmaker Brian De Palma, constantly accused of misogyny for movies such as Dressed to Kill (1980), Blow Out (1981), Body Double (1984), envisioned the female protagonist during the immersion years of the Second-Wave Feminism and the foundation of the Feminist Film Theory (1975). At the same time, as the director tends to appropriate published stories to create new scripts, identifying the web of knitted references in Phantom of the Paradise is essential for understanding all female and male characters in the movie